Independently ambulant, community–dwelling stroke survivors have reduced cardiorespiratory fitness, mobility and knee strength compared to an age- and gender-matched cohort*. Issue 3 (3rd April 2017) - Dunn, Ashlee; Marsden, Dianne L.; Van Vliet, Paulette; Spratt, Neil J.; Callister, Robin
Abstract : Background: Most exercise interventions for stroke survivors are designed for those who have substantial motor and functional disabilities. There remains a group of well-recovered stroke survivors who have yet to be investigated in terms of their physical capacity and fitness levels. Objective: To assess and compare the physical capacities of independently ambulant, community-dwelling stroke survivors to age- and gender-matched comparison participants. Methods: Data were obtained from 17 stroke survivors participating in the How FITSS? Trial, all with functional ambulatory category of ≥4 and a self-selected walking speed ≥0.8 m s −1 . An additional 17 healthy control participants were recruited. Cardiorespiratory fitness (CRF) was measured using oxygen consumption (VO2peak ), and additional measures of walking speed (m s −1 ), leg strength and body composition were also assessed. Differences between groups were assessed by matched pairs t -tests. Effect sizes were calculated using Cohen's d . Results: There were no significant differences in age, BMI, muscle mass or body fat between groups ( p  > 0.05). Peak VO2 was lower in the stroke group for the shuttle walk test ( p  = 0.037) and progressive cycle test ( p  = 0.019), as were all CRF test performance measures ( p  < 0.05). Stroke survivors walked significantly ( p  < 0.001) slower at both self-selected and fast speeds. Effect sizes of group differences for all leg strength variables were medium to large, with peak torque lower in the stroke group for all trials. Conclusions: Despite being independently ambulant and community dwelling, the CRF, walking speed and leg strength of this group were reduced compared to non-stroke comparison participants. These patients may benefit from undertaking targeted exercise programmes.